REVIEW AND ANALYSIS OF THE ELECTRONIC DATA COLLECTION SYSTEMS - Denisova, Ļubova; Augustova, Aija; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
The authors in this work provided an insight into the electronic data collection systems and the general information about the strengths, the weaknesses and the potential of exploration of both systems. The authors carried out an electronic data system description and the analysis is based on the research and comparison. As a result, a set of recommendations of the improvement of the both systems was provided.